Respiratory Arrest in an Obese Pregnant Woman with Hyperemesis Gravidarum - Ayumi Iwashita; Yosuke Baba; Rie Usui; Akihide Ohkuchi; Shigeaki Muto; Shigeki Matsubara (Case Reports in Obstetrics and Gynecology)
A pregnant, non-Japanese-speaking Peruvian, and, thus, with communication difficulty, suffered hyperemesis gravidarum and had respiratory arrest, requiring cardiopulmonary resuscitation. The obese pregnant woman (prepregnancy weight: 107 kg) had vomited and lost 15 kg in bodyweight over appropriately 2 weeks prior to the arrest but had not complained due to communication difficulty, which, together with her obesity, prevented a Japanese obstetrician from noticing her severe condition. 1,000 mL of low potassium fluid plus thiamine was administered. She became unable to stand, suggesting lower-extremity-proximal-muscle weakness, and then respiratory arrest occurred. Hypopotassemia (2.3 mEq/L), pulseless electrical activity, and muscle weakness suggested the presence of severe potassium deficiency, which may have caused respiratory muscle paralysis, leading to the respiratory arrest. Hypercapnea was severer than expected for compensatory hypoventilation, indicating the presence of concomitant severe hypoventilation, which may also have contributed to respiratory arrest. She recovered with electrolyte and volume replacement. Respiratory arrest can occur with hyperemesis gravidarum, and obesity and communication difficulties can prevent the early detection of severe conditions.